Faktor yang Berhubungan dengan Kepatuhan Membayar Iuran JKN Peserta PBPU Sektor Informal di Kelurahan Tlogosari Kulon - Azzahra Nur Azizah; Maharani, Chatila (LPPM Hang Tuah Pekanbaru, 2025)
Compliance in paying JKN (National Health Insurance) contributions is crucial for ensuring the sustainability of the program. In Semarang City, the number of non-compliant PBPU (Non-Wage Worker) participants continues to rise, from 35.99% in 2022 to 48.36% or 108,949 peoples in 2023, and increased to 109,345 peoples in 2024, with total arrears reaching IDR 107,206,921,401 in 2024. This study aimed to identify the factors associated with compliance in paying JKN contributions among PBPU participants in the informal sector in Tlogosari Kulon Village, Semarang City. The research used a quantitative analytical observational design with a cross-sectional approach. A total of 183 respondents were selected through purposive sampling. The study was conducted in February-March 2025. Data analysis included univariate, bivariate (chi-square test), and multivariate (multiple logistic regression analysis). The results showed that the factors associated with compliance in paying JKN contributions are the level of education, family income per member, number of family members covered by BPJS Kesehatan, payment method, perception of risk, perception of benefits of BPJS Kesehatan, history of catastrophic illness, knowledge about JKN, and understanding of compliance and penalties related to JKN services. This research is expected to help stakeholders develop strategies such as enhancing education quality and frequency, and empowering JKN cadres or community leaders as reminders to improve contribution compliance among PBPU participants.